Oxidative stress: The nexus of obesity and cognitive dysfunction in diabetes - Li, Huimin; Ren, Jing; Li, Yusi; Wu, Qian; Wei, Junping (Frontiers in Endocrinology, 2023)
Obesity has been associated with oxidative stress. Obese patients are at increased risk for diabetic cognitive dysfunction, indicating a pathological link between obesity, oxidative stress, and diabetic cognitive dysfunction. Obesity can induce the biological process of oxidative stress by disrupting the adipose microenvironment (adipocytes, macrophages), mediating low-grade chronic inflammation, and mitochondrial dysfunction (mitochondrial division, fusion). Furthermore, oxidative stress can be implicated in insulin resistance, inflammation in neural tissues, and lipid metabolism disorders, affecting cognitive dysfunction in diabetics.